DNA fingerprinting of selected black pepper (piper nigrum L.) varieties. - Manjunath Mogalayi (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2011)
Black pepper (Piper nigrum L.) famous as “Black Gold” and also known as “King of Spices” is one of the important agricultural commodities of commerce and trade in India since pre-historic period. The crop is the major source of income and employment for rural households in the predominantly pepper growing State of Kerala where more than 2.5 lakh farm families are involved in pepper cultivation. Karnataka, Tamil Nadu are the other major pepper producing States in the country. Kerala accounts for 80-90% of the total pepper production in the country. Idukki and Wynadu are the two major pepper producing districts in Kerala. Different cultivars/varieties are popular among the farmers and there phenotypic identity is not very distinct.